Pelatihan Pembuatan Pin Press Digital Bagi Siswa untuk Meningkatkan Keterampilan dan Menumbuhkan Semangat Wirausaha - Achmad Daengs GS; Rizky Khairunnisa Sormin; Zulia Almaida Siregar; Riki Winanjaya; Anjar Wanto (Forum Kerjasama Pendidikan Tinggi, 2023)
This PKM activity aims to develop the skills of Vocational High School (SMK) students in making digital pin presses through special training. Technology and mechanical skills are becoming increasingly important in today's digital era, and vocational schools have a key role in preparing students for the ever-changing world of work. The training was carried out at the Anak Bangsa Private Vocational School located in Simalungun Regency. In this activity, we designed and implemented intensive training for vocational school students on making digital pin presses. This training includes a basic understanding of digital technology, use of relevant hardware and software, as well as technical skills required in the manufacturing process. Apart from that, the team leader also provided material about the entrepreneurial spirit which was carried out using the Zoom application. The training method involves practical teaching and guidance from experienced instructors. The results of the activity show that this training was successful in improving students' skills in making digital pin presses. In addition, students also demonstrated improvements in their understanding of digital technology and its potential use in the world of work. It is hoped that this activity can make a positive contribution to developing the skills of vocational school students and help them prepare to enter an increasingly competitive job market. The results of this training can be used as a basis for developing similar training in other vocational schools and can be a reference for educational institutions and the government in efforts to improve the quality of vocational education in Indonesia.